Penerapan Filsafat Pendidikan Progresivisme dalam Kurikulum Merdeka - Khoirunnisa Khoirunnisa; Riska Nabela; M. Sahrial Efendi Lubis; Herlini Puspika Sari (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The application of the philosophy of progressive education within the Merdeka Curriculum aims to create a more student-centered education system that encourages active and contextual learning. Progressivism emphasizes the importance of hands-on experiences and the development of critical thinking skills through real projects and discussions. In the context of the Merdeka Curriculum, this approach allows students to explore their interests and talents more independently, with teachers acting as facilitators guiding the learning process. Through project-based learning, collaboration, and authentic assessment, the Merdeka Curriculum provides students with the opportunity to explore their interests and talents. This research identifies various strategies that educators can adopt to integrate the principles of progressivism, such as using active learning methods and allowing freedom in choosing learning materials. The implementation of the progressive philosophy presents several challenges, including teachers' readiness to adopt new roles, the need to adjust the curriculum to local contexts, and the availability of adequate resources. However, this application also offers significant opportunities to enhance the quality of education by producing graduates who are more adaptive, creative, and capable of solving complex problems. This study highlights how the application of progressive philosophy in the Merdeka Curriculum can increase student motivation, develop 21st-century skills, and prepare them for future challenges. Therefore, it is essential to continuously evaluate and develop this approach to align with the evolving times and national educational needs.